Sistem Informasi Manajemen Sebagai Alat Pengelolaan Penelitian Dosen - Joni, I Dewa Made Adi Baskara; Sandika, I Kadek Budi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 1 April 2016, 2016)
A lecturer at a university has the obligation to perform tri dharma college. One of the tri dharma is research. Research activities is a very important thing to be managed properly. Good management can improve the quality of the lecturer career that will have an impact on the quality of STMIK STIKOM Indonesia (STIKI) as an educational institution. This research has been through various stages, ranging from business process analysis, design until the implementation of the system. Based on the analysis of business processes in the current system found various problems. The main problem is on the process of research recapitulation. The running of manual system could be caused human error and generated inaccurate information and not real time. The system is designed using a structured design models starting from document flow diagrams, system flow diagrams, data flow diagrams until the entity relationship diagram. The bulit system has ranging features from master data management, management of research proposals until the management of the research report. All of these management processes have been designed to run systematically that could be minimized the error rate due to human error.
Keywords: Sistem; Informasi; Manajemen; Perancangan; Terstruktur